Some considerations on numerical methods for Cauchy singular integral equations on the real line - Capobianco, Maria Rosaria; Criscuolo, Giuliana (Mathematical Modelling and Analysis, 2024)
Two different direct methods are proposed to solve Cauchy singular integral equations on the real line. The aforementioned methods differ in order to be able to prove their convergence which depends on the smoothness of the known term function in the integral equation.